AUTONOMOUS NERVOUS SYSTEM-RELATED VITAL REACTIONS IN SHORT-DROP HANGINGS - Leković, Aleksa; Nikolić, Slobodan (Medicinski podmladak, 2024)
There are many anatomopathological signs forensic pathologists take into account in autopsy evaluation of deaths by hangings, having in mind one of the most important tasks: to prove the person was alive at the moment of suspension. Forensic medicine textbooks describe in detail many routinely observed findings, but some phenomena were not of particular interest. This may be, of course, due to the unreliability or impracticability of the finding interpretation. Nevertheless, some signs of vitality that may be related to the autonomous nervous system (ANS) in hangings could be useful. We may consider these as general ANS-related vitality phenomena, associated with the agonal sequence, and those directly associated with the specific neck region injury by the ligature. The former is primarily the non-specific increase in blood catecholamine levels and the hypersalivation with saliva dropping on the face skin from the lips’ angles, which is associated with agonal convulsions and deep terminal “abdominal” respirations. The latter, probably more interesting, is the so-called facies sympathique: the lesion of the sympathetic fibers in the neck region may lead to myosis and partial upper eyelid ptosis on the side of the lesion. However, this sign was not of great interest in research and remained incompletely understood regarding the postmortem appearance interpretation. This demands further studies but, if properly analyzed, may prove useful, as proof of vitality and for reconstructing the event, too, in case the other findings are subtle or absent.
Keywords: Hanging; Suicide; Autopsy; Forensic Pathology; Vital reaction; Autonomous nervous system and ANS; Hypersalivation; Agony; Facies sympathique; Myosis; Ptosis